2020
DOI: 10.5194/wes-2019-102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-design of an upwind rotor for a downwind configuration: design changes and cost evaluation

Abstract: Abstract. Within this work, an existing model of a Suzlon S111 2.1 MW turbine is used to estimate potential cost savings when the conventional upwind rotor concept is changed into a downwind rotor concept. A design framework is used to get realistic design updates for the upwind configuration as well as two design updates for the downwind configuration, including a pure material cost-out on the rotor blades and a new planform design. A full design load basis according to the standard has been used to evaluate th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…With a reduction in blade mass, the costs of the nacelle system were also reduced by 1.3%, and the complete turbine capital cost reduction was 1.7%. However, the aeroservoelastic OpenFAST simulations returned a 1.2% lower AEP for the downwind rotor caused by the reduced swept area during operational loading, consistent with prior findings 17,18 . This is reflected in Figure 3, which shows the two power curves and the difference between them before rated power.…”
Section: Rotor Redesignsupporting
confidence: 86%
See 4 more Smart Citations
“…With a reduction in blade mass, the costs of the nacelle system were also reduced by 1.3%, and the complete turbine capital cost reduction was 1.7%. However, the aeroservoelastic OpenFAST simulations returned a 1.2% lower AEP for the downwind rotor caused by the reduced swept area during operational loading, consistent with prior findings 17,18 . This is reflected in Figure 3, which shows the two power curves and the difference between them before rated power.…”
Section: Rotor Redesignsupporting
confidence: 86%
“…As for loads, recent numerical studies performed on a 2‐MW model with conventional aeroservoelastic models showed a decrease in the ultimate blade root flapwise moment, at the expense of an increase in fatigue loading 17,22 . Rotor thrust and tower base fore‐aft moments followed similar trends with lower ultimate loads but additional fatigue wear.…”
Section: Power Production and Loadsmentioning
confidence: 81%
See 3 more Smart Citations